The pejibaye palm (Bactris gasipaes H.B.K.) as an agroforestry component - Clement, Charles Roland (Agroforestry Systems, 1986)
The pejibaye palm was domesticated by the Amerindians as part of their indigenous agroforestry systems. The multiple uses of its fruit make it an attractive food species, while high production makes it an attractive economic proposition. Its growth habit is ideal for a canopy strata in some types of agroforestry schemes and, by controlling the number of stems to be maintained, may be modified to fit different species mixes. Several Brazilian mixed cropping experiments are mentioned, although results are not yet available. The Costa Rican experience with pejibaye * coffee mixed cropping is examined, with special reference to Tucurrique, Cartago. Two hectares of pejibaye, with coffee and banana are shown to lucrative. Research needs are discussed, with special emphasis on the question of multiple versus single stemmed plantings and modifications of the pejibaye ideotype for use in multi-stemmed, multi-species plantations. The pejibaye has significant potential for the small farmer and a greater potential if improved for both agroforestry and monoculture. © 1986 Martinus Nijhoff/Dr W. Junk Publishers.